Berpikir Kritis dalam Pembelajaran Fluida Dinamis: Tinjauan Sistematis Model Pembelajaran - Cindy Tyas Harvina; Parno; Ahmad Taufiq; Marlina Ali (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to identify learning models implemented to promote student’s critical thinking skills in fluid dynamics learning and synthesize evidence regarding their reported effectiveness. Using the PRISMA framework, seven empirical studies published between 2021 and 2025 and focusing on senior high school students were selected according to predefined inclusion criteria. The review examined student’s initial critical thinking conditions, instructional approaches, and reported learning outcomes. The findings indicate that student’s initial critical thinking skills in fluid dynamics were generally low to moderate, suggesting persistent difficulties in higher-order thinking processes. The reviewed studies implemented five instructional approaches, namely Problem-Based Learning, Guided Inquiry, RADEC, Metacognition Based Discovery Learning, and Think Pair Share, all of which were reported to support student’s critical thinking development. Several studies employing pretest–posttest measures reported moderate to high learning gains, while posttest-based studies showed higher critical thinking performance among students receiving innovative instruction. The reviewed evidence also suggests that students often experience difficulties in relating relationships among pressure, velocity, and flow rate to mathematical representations and scientific reasoning. Overall, student-centered instructional approaches contribute positively to critical thinking development in fluid dynamics learning, although their effectiveness varies across learning contexts and assessment indicators.